KERANGKA KONSEPTUAL: LIVE STREAMING SHOPPING DAN TRUST APAKAH BERPENGARUH TERHADAP IMPULSIVE BUYING? - Amalia Nursyamsiah; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (FEB Universitas Sam Ratulangi Manado, 2024)
Indonesia has 210 million internet users and become the countries with the highest number of internet users in the world. Business actors use the internet to carry out digital marketing through marketplace. The development of e-commerce in Indonesia has increased, e-commerce facilitates business actors with the new features that can stimulate consumers to purchase. This research aims to determine the relationship between live streaming shopping and impulsive buying through trust. This research uses questionnaire data from respondent, namely Telkom University’ students. This research uses quantitative research using SMART-PLS software and descriptive analysis techniques. The result state that live streaming shopping ultimately contributes and encourages consumers to make impulsive buying (Nurhaliza and Kusumawardhani, 2023).